Analysis of tannin and catechin levels in ethyl acetate extract of gambir twigs (Uncaria gambir Roxb.) using UV-Vis spectrophotometry - Marjoni, Mhd. Riza; Trijuanda, Suci Enika; Evani, Nhila Putri (Science Midwifery, 2025)
The utilization of gambir twigs (Uncaria gambir Roxb.) as a source of bioactive compounds is still relatively minimal, even though gambir has the potential to contain tannins and catechins, which enable it to possess antioxidant, anti-inflammatory, and antimicrobial activities. This study aims to analyze the tannin and catechin content of gambir twig extracts tested using the UV-Vis spectrophotometry method. Extraction was performed using the maceration method with ethyl acetate solvent, followed by qualitative analysis using FeCl3 reagent. Quantitative analysis was conducted using the Folin-Ciocalteu method to determine the tannin content at a wavelength of 742 nm and catechin analysis at a wavelength of 280 nm. The research results show that the extraction yielded a yield of 17.83% with a DER-native value of 5.60. Qualitative analysis with the FeCl₃ reagent gave a positive result, indicated by the formation of dark greenish-black spots, showing the presence of phenolic compounds. The tannin content was measured at 0.290% w/w, with the regression equation y= 0.0072x + 0.2172 (R²=0.9523), while the catechin analysis with the regression equation y= 0.0019x + 0.049 was 0.006%. The analytical method shows good sensitivity with a detection limit of 10.5563 µg/mL and a quantification limit of 35.1877 µg/mL. The results of this study provide important information about the potential of gambir branches as a source of natural bioactive compounds.